The JWST-SUSPENSE Ultradeep Spectroscopic Program: Survey Overview and Star Formation Histories of Quiescent Galaxies at 1 < z < 3 - Martje Slob; Mariska Kriek; Aliza G. Beverage; Katherine A. Suess; Guillermo Barro; Rachel Bezanson; Gabriel Brammer; Chloe M. Cheng; Charlie Conroy; Anna de Graaff; Natascha M. Förster Schreiber; Marijn Franx; et al. (The Astrophysical Journal)
We present an overview and first results from the Spectroscopic Ultradeep Survey Probing Extragalactic Near-infrared Stellar Emission (SUSPENSE), executed with NIRSpec on JWST. The primary goal of the SUSPENSE program is to characterize the stellar, chemical, and kinematic properties of massive quiescent galaxies at cosmic noon. In a single deep NIRSpec/MSA configuration, we target 20 distant quiescent galaxy candidates ( z = 1–3, H _AB ≤ 23), as well as 53 star-forming galaxies at z = 1–4. With 16 hr of integration and the G140M-F100LP dispersion-filter combination, we observe numerous Balmer and metal absorption lines for all quiescent candidates. We derive stellar masses (log M _* / M _⊙ ∼ 10.2–11.5) and detailed star formation histories (SFHs) and show that all 20 candidate quiescent galaxies indeed have quenched stellar populations. These galaxies show a variety of mass-weighted ages (0.8–3.3 Gyr) and star formation timescales (∼0.5–4 Gyr), and four out of 20 galaxies were already quiescent by z = 3. On average, the z > 1.75 [ z < 1.75] galaxies formed 50% of their stellar mass before z = 4 [ z = 3]. Furthermore, the typical SFHs of the galaxies in these two redshift bins ( z _mean = 2.2 [1.3]) indicate that galaxies at higher redshift formed earlier and over shorter star formation timescales compared to lower redshifts. Although this evolution is naturally explained by the growth of the quiescent galaxy population over cosmic time, number density calculations imply that mergers and/or late-time star formation also contribute to the evolution. In future work, we will further unravel the early formation, quenching, and late-time evolution of these galaxies by extending this work with studies on their chemical abundances, resolved stellar populations, and kinematics.